Health and well-being in the middle grades : research for effective middle level education - Main, Katherine M.; Whatman, Susan (Handbook of research in middle level education series., 2023)
"Current research around the middle grades has brought a heightened attention by teachers, policymakers, and researchers recognizing that this stage is a time when a students' health and social and emotional well-being directly impacts their academic progress. To date, school leaders and teachers have not been well served by explicit resources for middle grades education that focus on aspects of the health and well-being of young adolescent learners to support the planning of curriculum and teaching and to support teachers and leaders working with this age-group. The purpose of this research - based volume is to fill that gap and to enable school leaders, teachers, academics, and teacher candidates to develop successfully an understanding of the health and well-being aspects of young adolescent learners and provide them with the necessary tools and information to address the health and well-being needs of young adolescent learners. This call is for chapter submissions that report on empirical research when working with young adolescent learners and responding to their health and well-being"--